Impact of the pandemic at the Emergency Ward of the Police Pediatric Hospital: (from march 13th 2019 to july 14th 2019 and from march 14th 2020 to july 14th 2020) (Archives of Pediatrics of Uruguay, 2022)
Introduction: the WHO declared the SARS-CoV-2 COVID-19 pandemic on 3/11/2020. A Public Health Emergency was declared in Uruguay and as of 3/13/2020 and different measures were adopted to prevent the spread of the virus, including the establishment of reduced mobility measures. This led, among other things, to a decrease in attendance levels at all health centers, including pediatric emergency consultations.Objective: to describe the characteristics of the consultations in the Emergency Service of the Police Hospital during 3/14/20-07/14/20 within an epidemiological context and to compare it with the same period in 2019.Methodology: we carried out a retrospective descriptive observational study from March 14 to July 14, 2019 and 2020. We included all children and adolescents from 0 to 14 years old including those who consulted in the Emergency Service of the Police Hospital. We considered epidemiological, clinical and evolutionary variables. Data source: medical records. Statistical analysis: frequency distribution, summary measures and significance.Results: the absolute frequency of consultations in the period analyzed was 2,765 in 2019 compared to 576 in 2020.A 79% reduction in consultations was identified in 2020 compared to 2019. Respiratory infections decreased by 53%, even though obstructive bronchial crises did not. On the other hand, we recorded a significant increase 87.5% in trauma/cutting injuries. A significant rise of 427% in consultations for scabies was observed. No significant growth in consultations for mistreatment/abuse was identified.Conclusions: pediatric emergency consultations decreased compared to the previous year, which matches the international literature. Respiratory infections continue to be the main reason for consultation. There was a significant increase in both lesions and scabies, which can be linked to the confinement measures.
Keywords: SARS-CoV-2; Pandemics; Emergencies; COVID-19